INTEGRATION OF ANALYTICAL HIERARCHY PROCESS AND VIKOR TO ACHIEVE A SUSTAINABLE MANUFACTURING SYSTEM - Dwimas, Herdian (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2019)
Sustainability concept often used by big companies to help them sustain through the uncertainty of industrial’s scene. This research aims to design a precise guideline of how to implement sustainability concept by considering economic, environment, and social aspect as the main components of sustainability. Lean, green, and agile manufacturing will represent each aspect and will be used as primary indicators to contrive the concept’s guideline. VIKOR analysis was used to assign enablers and barriers of each indicator. This research was conducted at PT. XYZ Tbk, one of the national leading company in producing timber products such as plywood, fiberboard, and blockboard. As a result, This research proposed several alternative strategies based on selected enablers and barriers. The selected enablers are employee involvement, core competency, people and information, resource efficiency, and the selected barriers are lack of knowledge about lean, high short-term cost, power shortage, and lack of awareness.